Retrospective review of pyrocarbon radial head replacement - Richard S. Page, BMedSci, MBBS, FRACS (Ortho), FAOrthA (Elsevier, 2021)
Background: Radial head arthroplasty is the preferred surgical management for complex, unreconstructable radial head fractures. There has been increasing use of pyrocarbon prostheses, with potential tribology and modulus advantages over metallic counterparts. This study aims to assess clinical and radiological outcomes for radial head replacement after trauma using a modular, uncemented pyrocarbon prosthesis. Materials and Methods: Between September 2009 and March 2020, a consecutive series of 22 trauma cases were available for review. Patients underwent radial head arthroplasty using a pyrocarbon prosthesis (Ascension Modular Radial Head System, Austin, TX). Recorded outcomes included clinical assessment, radiological evaluation, and patient-reported outcome measures specific to elbow function. Results: Twenty-two patients (7 male, 15 female) with an average age of 51 years (range 21-64) were analyzed with a minimum 12 months of follow-up. All patients had complex radial head fractures, categorized as a Mason 3 or 4 injury. At follow-up, mean elbow range of motion included flexion 130° (range 100°-150°), extension 19° (0-50°), pronation 73° (30°-90°), and supination 70° (10°-90°). The mean Mayo Elbow Performance Index score was 83 (55-100), and Disabilities of the Arm, Shoulder and Hand score was 22 (2.5-60). Radiological evaluation showed 14 patients with asymptomatic proximal neck resorption and two patients with radiological stem loosening. In total, 3 of 22 implants were revised—2 were excised, and 1 revised to a long stem for traumatic implant fracture. Conclusion: Pyrocarbon radial head arthroplasty provided reliable functional results for patients after unreconstructable radial head fracture. The unique potential for fracture of the prosthesis should be considered in long-term follow-up, with appropriate activity advice to patients.